Nonequilibrium of the dense electric arc plasma cased by radiation transfer - Zhovtyansky, V.А.; Lelyukh, Yu.I.; Tkachenko, Ya.V. (Вопросы атомной науки и техники, 2012)
The results of the tomographic spectroscopy study of the free burning electric arc plasma between evaporating copper electrodes are presented briefly. The role of resonance radiation in departure of the dense plasma from the state of local thermodynamic equilibrium is evaluated. The transfer of radiation in plasma is taken into consideration unlike well-known Griem criterion. The results of numerical modeling demonstrate the effects of non-equilibrium between the ground, metastable and resonant levels.